2013
DOI: 10.1016/j.neuroimage.2013.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and structural connectivity within the default mode network relates to working memory performance in young healthy adults

Abstract: Studies of functional connectivity suggest that the default mode network (DMN) might be relevant for cognitive functions. Here, we examined metabolic and structural connectivity between major DMN nodes, the posterior cingulate (PCC) and medial prefrontal cortex (MPFC), in relation to normal working memory (WM). Metabolic connectivity, a correlation between FDG uptake in PCC and MPFC, was examined in groups of subjects with (relative to median) low (n=18) and high (n=17) performance on digit span backward test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 58 publications
(69 reference statements)
2
49
0
Order By: Relevance
“…This observation is consistent with a previously reported whole-brain voxel-wise analysis in the same groups. 10 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is consistent with a previously reported whole-brain voxel-wise analysis in the same groups. 10 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found support for the functional role of the DMN, a network that is deactivated during attention-demanding tasks, in verbal WM. 10 Here, we focused on task-positive regions, i.e., regions that are activated by a verbal WM task. 9 Under such conditions, the two previously reported DMN clusters were not identified as part of the (in nature task-positive) network of six BAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, however, increased integration of the DMN with a core region of this network was related to better neuropsychological performance. Interestingly, studies in other populations, such as in patients with Parkinson's disease (Disbrow et al., 2014; Tessitore et al., 2012), healthy older adults (Ward et al., 2014), and healthy controls (Yakushev et al., 2013) have reported that greater connectivity within the DMN is associated with better performance on different memory tasks. Our results are also consistent with recent findings suggesting that among patients with depression, but not healthy controls, better performance on a delayed recall trial of list learning was predictive of greater connectivity between the parahippocampus and subcortical structures (Rao et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, connectivity within the DMN is positively associated with verbal working memory among healthy adults (Yakushev et al., 2013), and with memory performance (using a memory composite score) among older adults (Ward et al., 2014). Healthy controls also demonstrated an association between CEN connectivity and superior performance on Trails B, a measure of alternating attention (Seeley et al., 2007).…”
Section: Introductionmentioning
confidence: 99%